Technological Leadership Behavior and Technological Formation as Predictors of Education 4.0 Competency Determination of Educators in Region XII: A Convergent Design - Simpal, Mohamad; Pidor, Sylvia (Journal of Interdisciplinary Perspectives, 2024)
This study determined the influence of technological leadership behavior and technological formation on Education 4.0 competency determination of educators in Region XII, Philippines. This study utilized mixed methods research, mainly convergent design. In the quantitative phase, adapted and validated survey questionnaires were employed, while an interview guide was utilized in the qualitative phase during in-depth interview (IDI) and focus group discussion (FGD). The statistical tools used in analyzing the quantitative data included mean, standard deviation, and multiple linear regression analysis, while thematic analysis was used for the qualitative data. The results revealed that the status of technological leadership behavior, technological formation, and Education 4.0 competency determination of educators were rated high. Moreover, technological leadership behavior and technological formation significantly influenced Education 4.0 competency determination. Further, facing limitations in the pedagogical and conceptual competencies related to Education 4.0, encountering inadequacy of resources, engaging in ICT upskilling and technology capacity-building activities, and becoming a proactive teacher were the themes generated from the lived experiences of educators. Furthermore, the themes extracted from the role of experiences that shaped their beliefs included learning is a continuous process, teaching is a vocation and bearing accountability to students. Likewise, manifesting resiliency, keeping a spirit of positivity, and embodying appropriate values were the themes generated from the experiences that shaped their attitude. Along with this, the themes that surfaced from the experiences that shaped the commitment of teachers involved visioning for knowledgeable students and manifesting passion for teaching. Finally, the nature of data integration revealed merging-converging.